Sterically Hindered Pyridine-Linked Sulfonated Polytriazoles: Fabrication of Membranes and Investigation of Single Fuel Cell Performance - Roy, Sambit; Ghanti, Bholanath; Ghosh, Debanjali; Pradhan, Debabrata; Voit, Brigitte; Banerjee, Susanta (ACS Applied Polymer Materials, 2022)
The semifluorinated sulfonated polytriazoles could integrate the benefits of both enhanced proton conductivity and chemical stability, which makes them one of the best choices for the fabrication of proton exchange membranes (PEM) for fuel cell applications. Herein we report a series of semifluorinated sulfonated polytriazoles, prepared from 2,2′-hindered pyridine functionalized nonsulfonated diazide (PYFAZ) and dialkyne (PYAK). The degrees of sulfonation of the polytriazoles (PYPYSH-XX) were varied by using DSSAZ as one of the sulfonated diazide comonomer in the polymer synthesis. The polymers showed a weight-average molecular weight of up to 450 »800 g·mol-1, and their chemical structures were confirmed by FTIR and NMR techniques. The solution cast membranes showed phase-separated morphology with well-defined hydrophilic and hydrophobic domains. The membranes were mechanically robust (tensile strength up to 65.5 MPa, Young modulus of 2.37 GPa), were thermally stable, and exhibited a very high oxidative stability of 48 h (PYPYSH-70). The elongation at the break of the membranes was above 13%, somewhat lower in comparison to that of Nafion-117. Nevertheless, it was possible to fabricate a good quality electrode membrane assembly. The membranes show proton conduction in the range of 95-184 mS·cm-1 (80 °C) and a power density of 599-966 mW·cm-2 (H2/O2) depending on their degree of sulfonation. All these results indicate the potential use of these membranes in PEMFCs.
CRIS-Team Scopus Importer:2023-03-20
Keywords: fuel cell; oxidative stability; sterically hindered pyridine; sulfonated copolytriazoles; trifluoromethyl groups